Strategie radzenia sobie z chorobą nowotworową w okresie chemioterapii = Coping strategies evaluated in oncological patients on chemotherapy treatment - Bożena Baczewska; Beata Kropornicka; Patrycja Mazurek; Bogusław Block; Ewa Krzyżanowska; Robert Łuczyk; Cecylia Olszak; Elżbieta Nowicka; Regina Lorencowicz; Bożena Muraczyńska (Kazimierz Wielki University, 2017)
Baczewska Bożena, Kropornicka Beata, Mazurek Patrycja, Block Bogusław, Krzyżanowska Ewa, Łuczyk Robert, Olszak Cecylia, Nowicka Elżbieta, Lorencowicz Regina, Muraczyńska Bożena. Strategie radzenia sobie z chorobą nowotworową w okresie chemioterapii = Coping strategies evaluated in oncological patients on chemotherapy treatment. Journal of Education, Health and Sport. 2016;6(11):205-220. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.166237 http://ojs.ukw.edu.pl/index.php/johs/article/view/3987       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 22.10.2016. Revised 30.10.2016. Accepted: 11.11.2016.       Strategie radzenia sobie z chorobą nowotworową w okresie chemioterapii Coping strategies evaluated in oncological patients on chemotherapy treatment   Bożena Baczewska1, Beata Kropornicka1, Patrycja Mazurek1, Bogusław Block2, Ewa Krzyżanowska1, Robert Łuczyk1, Cecylia Olszak1, Elżbieta Nowicka1, Regina Lorencowicz3, Bożena Muraczyńska4   1 Katedra Interny z Zakładem Pielęgniarstwa Internistycznego Wydział Nauk o Zdrowiu Uniwersytetu Medycznego w Lublinie 2 Katedra Psychoterapii i Psychologii Zdrowia Katolicki Uniwersytet Lubelski im. Jana Pawła II. OTS Lublin 3 Katedra i Zakład Pielęgniarstwa Neurologicznego Wydział Nauk o Zdrowiu Uniwersytetu Medycznego w Lublinie 4 Katedra Chirurgii i Pielęgniarstwa Chirurgicznego Wydział Nauk o Zdrowiu Uniwersytetu Medycznego w Lublinie       Słowa kluczowe: strategie radzenia sobie z chorobą, choroba nowotworowa, chemioterapia   Key words: strategies for coping with the disease, cancer, chemotherapy     Streszczenie Wstęp. Chemioterapia będąc długim procesem leczenia, niesie za sobą szereg skutków ubocznych. Wiele skutków ubocznych działania cytostatyków wpływa na psychikę człowieka. Pacjent w tym okresie stosuje różne strategie radzenia sobie z chorobą, które pozwalają mu przetrwać trudne chwile. Materiał i metoda. Badaniem objęto 123 pacjentów poddanych chemioterapii Centrum Onkologii Ziemi Lubelskiej w Lublinie. Zastosowano Skalę Przystosowania Psychicznego do choroby nowotworowej Mini-MAC oraz autorski kwestionariusz. Wyniki badań. Respondenci w 55,5% wykazują cechy zaabsorbowania lękowego. Zdecydowana większość pacjentów ukazuje cechy ducha walki (83,61%). Większość badanych (75,02%) nie wykazuje objawów bezradności i beznadziejności. Badani w 79,55% stosują zachowania zakwalifikowane do strategii pozytywnego przewartościowania. Częściej styl konstruktywny stosowały kobiety niż mężczyźni. Największe nasilenie stylu destrukcyjnego zanotowano dla osób chorych na nowotwory: narządów rodnych (36,26),  pęcherza (36,26) oraz sutka/piersi (34,71). Jeśli chodzi o styl konstruktywny, zaistniał on w każdym rodzaju choroby nowotworowej. Wnioski. 1. W badanej grupie pacjentów, poddanych chemioterapii dominują strategie ducha walki i pozytywnego przewartościowania, które są składowymi konstruktywnego stylu przystosowania się do choroby nowotworowej. 2. W okresie leczenia chemioterapeutykami u większości badanych występuje strach, będący następstwem możliwości nawrotu choroby nowotworowej. 3. Istnieje związek istotny statystycznie pomiędzy płcią i wiekiem ankietowanych, a funkcjonowaniem psychospołecznym. Kobiety miały wyższe nasilenie stosowania strategii bezradności- beznadziejności. Wraz z wiekiem nasila się zaabsorbowanie lękowe, poczucie bezradności- beznadziejności oraz maleje strategia ducha walki.       Abstract Backgroud. Chemotherapy is a long therapeutic process and as such it is bound to cause numerous side effects of treatment. Many of those adverse effects have impact on human mental condition, and contribute to patient's mental adjustment to their oncological problems. Material and Methods. The study was carried out in the group of 123 patients on chemotherapy treatment in St. John of Dukla Lublin Regional Oncology Centre. The patients were surveyed by Mental Adjustment to Cancer Scale Mini-MAC, and a questionnaire developed by the author for the purpose of research. Results. The results revealed 55.5% respondents showed features of anxious preoccupation, a considerable majority (83.61%) demonstrated fighting spirit, majority  of respondents (75.02%) did not show features of helplessness-hopelessness. The respondents (79.55%) presented behaviors qualified as positive redefinition strategies. The females were more constructive in that respect than males. The most destructive style was found in the group of patients with cancers affecting reproductive organs (36.26%), urinary bladder (36.26%), and breast cancer (34.71%). Constructive style of behaviors was observed in all types of cancer. Conclusions. 1. Strategies of constructive adjustment to cancer such as fighting spirit and positive redefinition were most frequent in the group of patients on chemotherapy.  2. The majority of patients on chemotherapy showed fear of possible recurrence of cancer. 3. Patient' sage and gender correlated statistically significantly with psycho-social functioning. Helplessness-hoplessness was more frequently observed in the females. Anxious preoccupation and a sense of helplessness-hopelessness increase with age, and fighting spirit decreases.